Causes of treatment failure and death in carcinoma of the lung. - Cox, J. D. (Yale Journal of Biology and Medicine, 1981)
Studies of patterns of failure and causes of death have been undertaken based upon the WHO histopathologic classification. In a randomized trial of thoracic irradiation +/- chemotherapy (hydroxyurea and CCNU), patterns of failure did not seem to differ by cell type; the largest group was "death without progression." A subsequent clinical trial of thoracic irradiation +/- cranial irradiation permitted a more detailed evaluation. Patients with squamous cell carcinoma had a higher rate of local failure than distant metastasis. Those with small cell carcinoma had a lower local failure rate and a high rate of distant spread. Patients with adenocarcinoma and large cell carcinoma had the lowest local failure rate, but had a high rate of distant metastasis. In 300 consecutive patients with autopsies, 75 percent with squamous carcinoma died of complications of the thoracic tumor and only one-quarter had extrathoracic dissemination; 30 percent with small cell carcinoma died of local tumor complications and 70 percent had carcinomatosis; 40 percent of patients with adenocarcinoma and large cell carcinoma died of intrathoracic complications, and 55 percent had distant metastases. Half the patients with small cell carcinoma, large cell carcinoma, and adenocarcinoma had brain metastases at autopsy. Future clinical trials should emphasize better control of the most common sites of failure.